Autonomic nervous system dysfunction in Parkinson's disease: relationships with age, medication, duration, and severity. Issue 10 (October 1993) - van Dijk, J G; Haan, J; Zwinderman, K; Kremer, B; van Hilten, B J; Roos, R A
Abstract : Heart rate variability at rest, during deep breathing, or standing up and with the Valsalva manoeuvre did not differ significantly between 67 patients with idiopathic Parkinson's disease (PD) and 31 healthy age matched controls. Blood pressure (BP) responses to standing up and sustained handgrip revealed diminished autonomic function in the PD group. In a preliminary analysis of the PD group older age, anti-Parkinson medication and higher Hoehn and Yahr (HY) stages were each associated with poor autonomic responsiveness. Disease duration was only related to the systolic BP fall on standing up. Multiple stepwise regression analysis showed that older age explained most of the variance of heart rate variability (up to 36%), and the only significant PD related factor was the use of medication, which explained less than 7%. The HY stage accounted for 12.7% of the variance in the standing up BP test, and the use of medication explained 10.6% of the variance of the systolic BP change in the sustained hand grip test. The unmedicated PD subgroup (n = 33), who had mild disease of short duration, showed no evidence of autonomic dysfunction. Cardiovascular autonomic dysfunction in PD is mild, mainly affects blood pressure responses, and occurs only in advanced cases.